PENGEMBANGAN VIDEO TUTORIAL PEMBUATAN SANDAL BERBAHAN KAIN PERCA PADA ELEMEN TECHNOPRENEUR FASE E DI SMKN 1 SOOKO - Rivi Angeline Permata Anggraini; Inty Nahari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Amid the development of the creative industry and entrepreneurship in the era of globalization, students of SMKN 1 Sooko still lack skills in processing fabric scraps into fashion products with commercial value. The scarcity of engaging learning media has prompted the development of video tutorial-based media to enhance students' skills while simultaneously fostering their entrepreneurial spirit. This study aims to: (1) describe the feasibility of a video tutorial on making sandals from fabric scraps, and (2) describe the skills of Grade X DPB 1 students at SMKN 1 Sooko after the implementation of the video tutorial media. The research employed a Research and Development (R&D) approach using the ADDIE model. The research subjects were 33 students selected through simple random sampling, with a one-shot case study design. The instruments included expert validation questionnaires for material experts, media experts, and a psychomotor assessment sheet. The resulting product was a video tutorial lasting more than 8 minutes, created using CapCut, which included an introduction, tools and materials, step-by-step sandal-making procedures, and a closing segment, with adequate audio-visual quality. The results showed that the video tutorial media was declared highly feasible for use, with an average validation score of 3.89. Its implementation with 33 students yielded an average score of 84, with a mastery rate of 90.9%, proving that this media is effective in improving students' conceptual understanding, practical skills, and learning motivation.